Prevalence of hypertension among the elderly Malays living in rural Malaysia - Rashid, AK (Australasian Medical Journal, 2011)
BACKGROUND: We are living in an ageing world. The prevalence of hypertension which is an established risk factor for cardiovascular disease and stroke increases with age. The aim of the study was to determine the prevalence of hypertension among the elderly Malays living in rural parts of north Malaysia. METHOD: This cross-sectional study was conducted among the elderly (aged ≥60) Malay residents living in 22 villages in a northwestern state called Kedah in Malaysia from 2007 to 2009. Kedah has one of the highest rates of elderly population in the country. Data was collected by trained research assistants. Besides the baseline demographic information, blood pressure was measured using standardised methods using a manual sphygmomanometer. RESULTS: The response rate was 97.7%. The prevalence of hypertension among the elderly in these villages was 54.5% (228), 118 (28.2%) were known to be hypertensive and were on medication and an additional 110 (26.3%) respondents were newly diagnosed. Elevated mean systolic (146.17 ± 25.23) and diastolic (89.68 ± 15.60) blood pressure was noted among the known hypertensive. There was an almost fourfold risk (OR 3.64) of having uncontrolled blood pressure among the known hypertensive on treatment. Those with malnutrition were at an almost twofold at risk of being hypertensive (OR 1.73). Binary logistics regression showed occupation (OR 1.65), marital status (OR 2.32) and body mass index (BMI) (OR 1.62) as significant predictor variables. CONCLUSION: Screening the elderly for hypertension will benefit this group of people by reducing the morbidity and mortality associated with this condition